UJI MODEL PENGEMBANGAN KARIER, LINGKUNGAN KERJA, PENGAWASAN TERHADAP MOTIVASI KERJA DAN IMPLIKASINYA PADA KINERJA KARYAWAN DUMA MOTOR WAY HALIM BANDAR LAMPUNG - Yohanes P Kumagaya (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
Existing human resources must be processed in order to become a central force that candrive the organization. Various cases of organizational failure if traced the cause is more oftencaused by human factors involved.Some conditions that can evoke the spirit of the work is in the form of career development,work environment and supervision that would have an impact on employee performance. High laborproductivity for employees is necessary in any organization in an effort to achieve the goal.Partial result of the discussion, it is known that there is a relationship between career development,work environment, motivation and performance, while the control has no effect on employeeperformance. However, all the independent variables simultaneously affect the dependent variable.